Production of educational resources for media education in schools: teachers’ perceptions and needs - Matos, Armanda P. M. (2025)
The relevance of media education has been increasingly recognized in the international context as well as in Portugal. Particular attention is given to children and young people, placing considerable responsibility on schools and teachers to contribute, from an early age, to the development of informed citizens, effective communicators, and active participants in the digital culture. The primary objective of the research conducted was to understand the perceptions of primary and secondary school teachers regarding media education and their role, as well as the role of the school, in promoting students’ digital and media literacy. Additionally, the study sought to examine teachers’ training and needs in this area, thereby gathering useful information to guide the development of educational resources. Following a non-experimental and descriptive methodology, based on data obtained from an online questionnaire created by the research team, it was concluded that teachers place great importance on media education, recognize the role of the school and themselves in students’ development, but also state that they have insufficient training in this field. Based on these results, two educational resources were developed: a book and a mobile application, designed to support teachers in addressing the challenge of implementing media education in schools.